Sustainable strategies for the communes of Manantiales and El Arroyo as adaptive territories in the face of climate change - Velásquez Salbatierra, Jenifer Valeria (2026)
Climate change generates disproportionate impacts in territories with high environmental exposure and limitedadaptive capacity. In the communities of Manantiales and El Arroyo, and in the canton of Montecristi(Ecuador), this vulnerability is exacerbated by the local economy's dependence on natural resources, thescarcity of adaptive infrastructure, and weak institutional coordination. Given this context, the study aimedto propose sustainability strategies that contribute to transforming the territory into a more adaptive spacetowards clime change, based on a diagnosis derived from semi-structured interviews with institutional representatives,population surveys, and statistical and thematic analyses. The analysis was structured aroundfour main problems: water scarcity and management, unsustainable production practices, weak social cohesion,and fragmented environmental governance. The results show that drought and rising temperaturesaffect the community of Manantiales more severely, while flooding predominates in El Arroyo. Furthermore,existing initiatives such as reforestation and water management are characterized by poor coordination andlimited technical support. Based on this assessment, sustainability strategies were proposed to strengthenlocal resilience, among the ones which outstand are community-based water management, sustainabletourism, inter-institutional partnerships, environmental education, and differentiated territorial planning. Thestudy concludes that effective collaboration between communities and institutions is key to move forward onmore adaptive rural areas in the face of climate change.